Metabolomics Investigation of Vitamin a Deficiency in a Rodent Model (P02-016-19). (13th June 2019) - Miyuki-Johnson, Catherine; Wilhelmson, Baylee; Gannon, Bryan; Fanter, Rob; Pedersen, Theresa; Tanimuhardjo, Sherry; Newman, John; Frano, Michael La
Abstract: Objectives: Vitamin A (VA) is an essential micronutrient with key roles in many biological processes, including growth, vision, reproduction, and immunity. While VA deficiency effects these physiological roles, the impact on many metabolic pathways are poorly studied. Since VA deficiency is a leading cause of morbidity and mortality throughout the world, a more comprehensive understanding of deficiency-associated metabolic alterations is needed. Here we investigate changes in metabolism associated with VA status in a rodent model using targeted metabolomics. Methods: Male Mongolian gerbils ( n  = 8/group) were group housed (2−3/cage) during VA depletion and treatment (2/cage). After 28 d depletion, remaining gerbils were weight-matched and allocated to treatment groups. The VA positive group (VA+) was fed white maize and 40 µg retinyl acetate in ∼50 µL cottonseed oil daily, while the VA deficient group (VA-) received white maize and ∼50 µL cottonseed oil. Liver retinol concentrations were measured by HPLC. Liver samples were analyzed by LC-MS using six targeted assays for primary metabolomics, aminomics, bile acids, oxylipins, endocannabinoids, and sphingoid bases. Results: Hepatic retinol concentrations were lower in the VA- group ( P  < 0.001). Of 277 identified metabolites, the cardiovascular risk associated trimethylamine-N-oxide and, numerous bile acids, including cholic acid, chenodeoxycolic acid, glycocholic acid, and tauroursodeoxycholic acid, were lower in this group ( P  < 0.05). Components of DNA, including purine deoxyribonucleosides deoxyadenosine ( P  < 0.02) and deoxyguanosine ( P  < 0.006), were differentially altered. Furthermore, the VA- group had lower nucleosides cytidine and the uracil derivative carbomoyl-beta-alanine ( P  < 0.05). Numerous acylcarnitines, vital for energy utilization of fatty acids, were also changed. Conclusions: A number of hepatic metabolites were altered by deficiency whose connection to VA status has not been investigated previously. Future studies that test the direct biological impact of these changes with VA status are necessary. Funding Sources: USDA Intramural Project 2032-51530-022-00D, NIH U24 DK097154, Cal Poly SURP